Adherence to First-Line Intravesical Bacillus Calmette-Guérin Therapy in the Context of Guideline Recommendations for US Patients With High-Risk Non-muscle Invasive Bladder Cancer - Franklin D. Gaylis; Bruno Emond; Ameur M. Manceur; Anabelle Tardif-Samson; Laura Morrison; Dominic Pilon; Patrick Lefebvre; Lorie A. Ellis; Hiremagalur Balaji; Andrea Ireland (Journal of Health Economics and Outcomes Research, 2024)
# Background Bacillus Calmette-Guérin (BCG) can reduce recurrence and delay progression among patients with high-risk non–muscle invasive bladder cancer (NMIBC), but is associated with a substantial emotional, physical, and social burden.